The Dynamics of Slido to Promote Learning in Rural University Classrooms - Adebola, Oyinlola Omolara (Research in Social Sciences and Technology, 2024)
Slido is an interactive online platform facilitating active learning in rural university settings. Rural universities often need more resources, including access to technology and opportunities for diverse pedagogical approaches. Traditional lecture-based teaching predominates due to these constraints, which can hinder student engagement and learning outcomes. Slido offers a solution by leveraging technology to enhance interaction, collaboration, and participation within the classroom environment. This study, therefore, adopted the Slido application to promote active learning in one of the rural university classrooms within South African higher education. Active learning methodologies have gained widespread recognition for their effectiveness in engaging students, fostering more profound understanding, and promoting critical thinking skills. However, implementing such strategies, especially in rural university classrooms, can pose unique challenges. Through features such as live polls, quizzes, and audience Q&A sessions, Slido enables instructors to create dynamic learning experiences that encourage active participation from students. In rural contexts where class sizes may be smaller and student diversity limited, Slido provides an avenue for inclusive participation and allows even the most reserved students to contribute anonymously. Hence, the qualitative study adopted a transformative paradigm as a lens and approached it through active learning designed by Action Research. Furthermore, the study was a two-year project involving third-year business studies students and their transition to, and completion of, their fourth year of study. Seven students were selected as the participants, and data was generated through a Focus Group discussion and analyzed using Thematic Analysis. The study revealed that Slido promotes activeness among students in the module selected in the rural university. In conclusion, Slido offers a promising solution for promoting active learning in rural university classrooms. The study recommends that lecturers should be empowered in terms of resources and training to infuse technology into teaching.